Therapy for Dupuytren’s Disease (II): Collagenase Therapy vs. Limited Fasciectomy—A Long-Term Comparative Study - Nikolaus Wachtel; Francesca Romana Dingler; Constanze Kuhlmann; Sinan Mert; Elisabeth Maria Haas-Lützenberger; Verena Alt; Nicholas Moellhoff; Riccardo Giunta; Wolfram Demmer (Life)
Background: Dupuytren’s disease (DD) is a systemic connective tissue disorder of the palm, predominantly affecting men of Northern European or Caucasian origin over 55. In addition to conventional surgery, Dupuytren’s contracture can be treated in a minimally invasive way by injecting bacterial collagenase into the cord. However, studies on the long-term success rate when compared to the gold standard, surgical limited fasciectomy, are limited. Methods: This monocentric retrospective study examined 35 patients who had been treated with bacterial collagenase for Dupuytren’s contracture, conducting a long-term follow-up after an average of 5.7 years. The results were compared to a control group of 40 patients treated with surgical limited fasciectomy on average 5.5 years ago. Finger extension (Tubiana stage), strength, sensitivity, the effect of possible risk factors, and patient-reported outcome measures (PROMs) were compared between the two groups. Results: The long-term results after therapy for DD showed a significant reduction in the Tubiana stage for both groups (p < 0.001). Additionally, we observed a longer mean preintervention Tubiana stage and a better long-term improvement in the Tubiana stage for patients with limited fasciectomy when compared to the collagenase group. (both p < 0.001). Neither grip strength nor the pinch test showed significant differences when compared within each group or when comparing both groups. Both the treated and untreated fingers of patients with limited fasciectomy had a superior two-point discrimination (p < 0.001). For the URAM questionnaire, we observed a significantly better result in the control group (p < 0.01). Retrospectively, significantly more patients in the collagenase group would not choose the same therapy to treat DD (35 vs. 8%; p < 0.05). Conclusions: The two therapy options should be seen as complementary for the treatment of DD. Collagenase therapy seems a sensible option for DD with an earlier Tubiana stage and contractures that predominantly affect the MCP joint. Contractures with higher Tubiana stages that also affect the PIP joint should predominantly be treated with limited fasciectomy.